Radiological Spectrum of von Hippel-Lindau disease – A Case Report (Indian Journal of Case Reports, 2015)
Von Hippel-Lindau (VHL) disease is an autosomal dominant genetic disorder resulting from inactivation of tumor suppression genes located at the chromosome 3p 25.5. VHL comprises of many benign and malignant tumors along affecting various systems of the body with variable manifestations. A wide variation in radiological spectrum is seen as per the involvement of particular system or organ. The imaging modalities like Ultrasonogrphy (USG), Computerized Tomography (CT) and Magnetic Resonance Imaging (MRI) play an important role in diagnosing and treating the affected individuals. These also play equally important role in the screening and follow up of such cases. We present a case of an 18 year old female, who was diagnosed with VHL at the age of 10 years, where imaging modalities helped her management and follow up.